Learning media development to improve students' spatial mathematical ability assisted by mobile phones using Augmented Reality - Yunianto, Yunianto; Cahyono, Adi Nur (Department of Mathematics, Universitas Negeri Semarang, 2021)
The purpose of this study was to describe the development of learning media to improve the Students' Spatial Mathematical Ability assist mobile phones using augmented reality and to determine the effectiveness of learning media assisted by mobile phones using augmented reality in team assisted individualization learning to improve students' mathematical spatial abilities. The development model used in this study is the ADDIE development model. ADDIE development stages are to Analyze, Design, Development, Implementation, and Evaluation. The population of this study was students of 8th grade at MTs Negeri 5 Magelang. The sample was taken from two classes with a random sampling technique from the population of 8th grade at MTs Negeri 5 Magelang. The results are: (1) a learning media has been developed in the form of an android application that uses augmented reality, which is named Bangun Ruang AR as a support for learning mathematics in build flat side space material. After going through the review and evaluation stage by media and material experts, the AR application is suitable to be used as a support for learning mathematics in build flat side space material with an eligibility percentage of 91.5% and included in the very good criteria and (2) The use of application learning media Bangun Ruang AR in Team Assisted Individualization learning effectively to improve students' mathematical spatial abilities, which is aimed at (a) Students' mathematical spatial abilities in team assisted individualization learning with learning media assisted by mobile phone using augmented reality achieve completeness; (b) There is an increase in students' mathematical spatial abilities in team assisted individualization learning with learning media assisted by mobile phone; (c) Students 'mathematical spatial abilities in team assisted individualization learning with learning media assisted by mobile phone are better than students' mathematical spatial abilities in conventional learning.